Penguatan Literasi Keuangan pada Siswa SMA Assa’adah - Zulpahmi; Sumardi; Edi Setiawan (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Everyone has a different level of financial literacy. It is important to instill financial literacy from an early age to know or manage finances so that they are healthy in the future. Likewise with this activity where the target is Assa-adah High School students, whose average age is 16-17 years. The purpose of service activities is; 1) Providing financial knowledge to Asa'adah High School students, and 2) Increasing awareness of financial management in making financial decisions for students. The Implementation Method consists of; Program Socialization, Implementation, Monitoring and Evaluation. Based on the results of the activities that have been running, there has been a significant increase in the financial literacy of Assa'adah High School students. This is evidenced from the results of questions and answers between the speakers and the participants, initially the participants did not know how to manage finances properly and correctly.